PERAN PERANGKAT DESA DALAM AKUNTABILITAS PENGELOLAAN DANA DESA (Studi Pada Desa Lakan Bilem Kecamatan Nyuatan Kabupaten Kutai Barat) - Danna Solihin, Janiel Lukisyo, Titin Ruliana, (EKONOMIA, 2020)
The village budget obtained by the village government is Rp. 2,302,056,400. of course it requires good management so there is no fraud. So that the role of the village apparatus is needed to help the village head in managing village funds. Considering that in terms of village fund management, it does not rule out the possibility of risk of errors both administrative and substantive which can lead to legal problems due to insufficient competency of village heads and village officials in Lakan Bilem Village in terms of planning, administration, reporting and accountability village finance.The purpose of this study is to find out the role of village officials to play a role in the accountability of the Village Fund management in the village of Lakan Bilem, Nyuatan Subdistrict of the Year 2018. According to permendagri No 113 of 2014 reviewed from Planning, Implementation, administration, reportin, accountability.The analytical tool used is Permendagri No 113 of 2014 in Sujarweni (2015: 18-20) calculating using Dean J. Champion Formula.Based on the results of the analysis and discussion on the research, the conclusions obtained are as follows. The role of the village officials in terms of planning was 83.33%, implementation was 73.91%, administration was 81.67%, reporting was 83.33%, accountability was 76.67% that is meantÂ it had played a good role according on permendagri no 113 of 2014